Different types of biosensors and their features - Siediuko, D. V.; Haluzinska, Y. I. (Problems of Environmental Biotechnology, 2016)
Biosensor technology is a powerful alternative to conventional techniques. Biosensors are analytical devices that respond selectively to analytes in an appropriate sample and convert their concentration into an electrical signal via a combination of a biological recognition system and an electrochemical, optical or other transducer. Different types of biosensors are described in this article. The main features of them are compared. Also mentioned the main areas of its application.